Environmental and socioeconomic assessment of textile products consumption in Brazil - relationships with international trade - Giacomin, Alessandra (2021)
Textile products drive a significant portion of the world economy, providing jobs, and being present in every aspect of our lives in all countries around the world. However, in its production, issues related to environmental and social pressures emerge. Taking into consideration the growing concern related to environmental and social impacts, it is necessary to address the issue of emissions generated indirectly by the sectors that supply the textile industry. This work has carried out an environmental and socioeconomic assessment of the consumption of textile products in Brazil, considering the relationship with international trade. The methodology used was the Multi-Regional Input-Output (MRIO) analysis, and the database used was Exiobase 3, for the year 2011. It was possible to conclude that most of the indirect impacts related to the textile industry are domestically generated. In the category of climate change and primary energy consumption, the sector that stood out was natural gas, with 51% of CO2 emissions and 33% of energy consumption. The largest share of indirect jobs is generated in the commercial sector with 34%, and the largest number of indirect employees are male with medium skill level, which represents 33%, followed by workers from the vulnerable class (self-employed) with 27%. Based on this analysis, it was possible to identify the greatest limitations related to socio-environmental aspects and the possible solutions to be adopted for this sector.